The Boy is Back - Cabot, Meg (New York : William Morrow, 2016)
"A scandal brings celebrity golfer Reed back home to the small town, the crazy family, and first love he once left behind."
Keywords: Golfers -- Fiction; Man-woman relationships -- Fiction; Homecomings -- Fiction; Golfers; Man-woman relationships; Fiction; Domestic fiction